Determining the Methods of Financing Health care Costs among Hospitalized Diabetic Patients in Different Types of Insurances - N Hassan Nejad (Tehran University of Medical Sciences, 2013)
Abstract: Background: Today one of the main problems low or middle income families face is financing healthcare costs. This article studies the methods of of financing health care costs among hospitalized diabetic patients in different types of insurances. Materials & Methods: This is a causal-comparative study. The variables consist of comparative (health care costs) and categorical(different insurance types including: Iran health insurance , social security and others) variables. A researcher-made questionnaire was used to collect needed data . The data were analyzed by one-way ANOVA , Duncan`s statistical test test of Danken and T-test. Results: The results indicated a significant statistical differences between all types of insurance assessed by cost variables. Also the significant differences between patient`s out of pocket expenses ratio of direct costs (p<0.01،F=19.37) and their ratio of total costs (F=25.36, p<0.01) were detected in three types of insurances . Patient`s out of pocket of total cost was 59.55%, 50.34% and 32% in Iran health insurance, social security and other types respectively. Conclusion: In spite of all invested deal of efforts to improve health indices and health care services availability ,health care system is still faces main challenges of providing financial resources and protecting against financial burden on families . Developing a public health insurance and improving health insurance coverage would be helpful for providing financial resources of health care system.